Honeycomb Films with Core-Shell Dispersed Phases Prepared by the Combination of Breath Figures and Phase Separation Process of Ternary Blends - Del Campo, A (Langmuir : the ACS journal of surfaces and colloids, 2017)
Herein, we propose a strategy to fabricate core-shell microstructures ordered in hexagonal arrays by combining the breath figures approach and phase separation of immiscible ternary blends. This simple strategy to fabricate these structures involves only the solvent casting of a ternary polymer blend under moist atmosphere, which provides a facile and low-cost fabrication method to obtain the porous structures with a core-shell morphology. For this purpose, blends consisting of polystyrene (PS) as a major component and PS40-b-P(PEGMA300)48 amphiphilic copolymer and polydimethylsiloxane (PDMS) as minor components were dissolved in tetrahydrofuran and cast onto glass wafers under humid conditions, 70% of relative humidity. The resulting porous morphologies were characterized by optical and confocal Raman microscopy. In particular, confocal Raman results demonstrated the formation of core-shell morphologies into the ordered pores, in which the PS forms the continuous matrix, whereas the other two phases are located into the cavities (PDMS is the core while the amphiphilic copolymer is the shell). Besides, by controlling the weight ratio of the polymer blends, the structural parameters of the porous structure such as pore diameter and the size of the core can be effectively tuned